P09.02 Modular P329G-binding CAR T cells engineered to recognize human effector-silenced antibodies carrying a P329G Fc-mutation for targeting of solid tumor antigens. (21st September 2022) - Stock, S; Benmebarek, M; Kluever, A; Darowski, D; Jost, C; Stubenrauch, K; Benz, J; Freimoser-Grundschober, A; Moessner, E; Umana, P; Subklewe, M; Endres, S; et al.
Abstract : Background: Chimeric antigen receptor (CAR) T cell therapy revolutionized the treatment of patients with B cell and plasma cell malignancies. However, treatment success is still limited by treatment-associated toxicities and antigen-negative relapse after an initial complete remission. Moreover, efficacy of CAR T cell therapy is insufficient in solid tumors. Modular CAR T cells in combination with CAR-adaptor molecules have the potential to mitigate severe adverse events and overcome antigen escape, so that various modular platforms are currently under investigation. To enable an optimized modular CAR T cell platform, we developed a P329G-targeting CAR. This novel and modular CAR targets the P329G mutation in effector-silenced human antibodies of the IgG1 subtype carrying P329G L234A/L235A (P329G LALA) mutations in the Fc part. These P329G LALA mutations are rendering the Fc part inactive for binding to Fc-gamma receptors or complement binding and are clinically validated by application in more than 20 Fc-silenced clinical stage therapeutic (bispecific) antibodies. Materials and Methods: A scFv-based P329G-CAR.CD28.CD3zeta CAR vector system was generated and used in primary human T cells of healthy donors. P329G-targeting CAR T cells were combined with antibodies of the IgG1 subtype carrying P329G LALA mutations in the Fc part. Effector functions of P329G-targeting CAR T cells combined with the respective binders were compared to conventional, directly targeting CAR T cells. Epidermal growth factor receptor (EGFR), mesothelin (MSLN) or HER2/neu were used as target antigens. Mesothelioma, pancreatic, and breast cancer cell lines expressing the respective tumor antigens were used as target cell lines in in vitro and in vivo experiments. Results: CD16-CAR T cells recognizing the Fc part of antibodies can be unspecifically activated by human IgG, while P329G-targeting CAR T cells can only be activated in presence of the P329G mutation. Combined with a MSLN-directed antibody carrying the P329G mutation in the Fc part, P329G-targeting CAR T cells exhibited sufficient in vitro and in vivo effector functions against pancreatic cancer and mesothelioma cell lines compared to conventional MSLN-targeting CAR T cells. P329G-targeting CAR T cells combined with a HER2-recognizing antibody showed substantial in vitro proliferation and activation as well as cytotoxic capacity and cytokine production against different HER2 positive breast cancer cell lines. A complete tumor eradication and survival of immunodeficient mice in a HCC1569 breast cancer xenograft mouse model could be seen. Effector functions of P329G-targeting CAR T cells were comparable to conventional HER2-targeting CAR T cells. P329G-targeting CAR T cells mediated in vitro and in vivo effector functions in a modular and reversible fashion. Conclusions: Taken together, we showed the introduction of a novel and modular platform for CAR T cell therapy. P329G-targeting CAR T cells combined with effector-silenced tumor antigen-binding antibodies of the IgG1 subtype carrying the clinically validated P329G LALA mutations in the Fc part can mediate profound in vitro and in vivo effector functions in various solid tumor models, warranting further clinical translation of the concept. Disclosure Information: S. Stock: A. Employment (full or part-time); Significant; University Hospital of Munich (LMU). C. Other Research Support (supplies, equipment, receipt of drugs or other in-kind support); Modest; Else Kröner-Fresenius Stiftung. M. Benmebarek: A. Employment (full or part-time); Significant; National Cancer Institute (NCI). A. Kluever: None. D. Darowski: A. Employment (full or part-time); Significant; Innovent. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Innovent, Roche. C. Jost: A. Employment (full or part-time); Significant; Athebio AG. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Roche. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; Athebio AG. K. Stubenrauch: A. Employment (full or part-time); Significant; Roche. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; Roche. J. Benz: A. Employment (full or part-time); Significant; Roche. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; Roche. A. Freimoser-Grundschober: A. Employment (full or part-time); Significant; Roche. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; Roche. E. Moessner: A. Employment (full or part-time); Significant; Roche. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; Roche. P. Umana: A. Employment (full or part-time); Significant; Roche. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; Roche. M. Subklewe: A. Employment (full or part-time); Significant; University Hospital of Munich (LMU). B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Amgen, BMS, Gilead, Miltenyi, MorphoSys, Novartis, Roche, Seattle Genetics. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Modest; Amgen, BMS, Gilead, Novartis, Pfizer, Takeda. F. Consultant/Advisory Board; Modest; Amgen, BMS, Gilead, Janssen, Novartis, Pfizer, Seattle Genetics, Takeda. S. Endres: A. Employment (full or part-time); Significant; University Hospital of Munich (LMU). B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Deutsche Forschungsgemeinschaft, Elitenetzwerk Bayern, Bio-M, TCR2 Inc. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Significant; Else Kröner-Fresenius Stiftung, Paul-Martini-Stiftung. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Carina Biotech Ltd. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; TCR2 Inc. F. Consultant/Advisory Board; Significant; Gilde Healthcare. C. Klein: A. Employment (full or part-time); Significant; Roche. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; Roche. S. Kobold: A. Employment (full or part-time); Significant; University Hospital of Munich (LMU). B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; European Union, Hector Foundation, Elite Network of Bavaria, Melanoma Research Alliance, EKFS, German Cancer Aid, Ernst-Jung-Stiftung, German Excellence Initiative, BMBF, Research Council, DFG, SFB-TRR 338/1, Fritz-Bender Foundation, José-Carreras Foundation, Bio-M, TCR2 Inc. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Modest; BMS, GSK. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Significant; Novartis. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Carina Biotech Ltd. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; TCR2 Inc. F. Consultant/Advisory Board; Modest; Tabby therapeutic Itd. F. Consultant/Advisory Board; Significant; Novartis, TCR2 Inc.